Aerosolised ribavirin in patients with advanced cryptogenic fibrosing alveolitis: a pilot study. Issue 1 (January 1993) - Agustí, C; Xaubet, A; Ballester, E; Alarcón, A; Picado, C
Abstract : BACKGROUND: A report has recently been published concerning a patient with a cryptogenic fibrosing alveolitis who showed a striking improvement after being treated with the antiviral drug ribavirin (tribavirin, Virazid). The objective of this study was to further evaluate, in an open trial, the efficacy of rivabirin in cryptogenic fibrosing alveolitis. METHODS: Ten patients (eight women) with advanced cryptogenic fibrosing alveolitis received aerosolised ribavirin (6 g/day for 15 days). Chest radiographs, lung function, and severity of dyspnoea were evaluated before and after two weeks of rivabirin treatment and also at three and 12 months. RESULTS: No differences in radiographs, lung function impairment, or severity of dyspnoea were found after treatment. No side effects were detected. CONCLUSIONS: Administration of high doses of aerosolised ribavirin has no beneficial effects in patients with advanced cryptogenic fibrosing alveolitis.